1996
DOI: 10.1111/j.1398-9995.1996.tb04621.x
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylaxis from cow's milk casein

Abstract: The case of a 35-year-old woman who suffered anaphylaxis after the ingestion of milk or milk-containing products is presented. Symptoms also appeared after the patient used a cosmetic which contained casein. Skin prick tests, specific IgE measurement, and immunoblotting were carried out with cow's milk extract, and its purified proteins: casein, beta-lactoglobulin, and alpha-lactalbumin. Specific IgE to cow's milk casein was detected with the three tests. Immunoblotting revealed one band of 24 kDa approximatel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

1999
1999
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 10 publications
0
7
0
Order By: Relevance
“…However, some studies have indicated that children with CMPA have higher concentrations of specific IgE antibody to proteins comprising the whey fractions of milk [8] while IgE directed to the proteins in the casein fraction appeared to be dominant in older children and adults with CMPA [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…However, some studies have indicated that children with CMPA have higher concentrations of specific IgE antibody to proteins comprising the whey fractions of milk [8] while IgE directed to the proteins in the casein fraction appeared to be dominant in older children and adults with CMPA [9,10].…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, in vitro measurement is preferred in patients with skin diseases such as AD or urticaria. In addition, numerous studies have suggested that the component is the best discriminator between persistent and transient CM allergy [6, 8, 11]. Severe reactions to CM can be predicted by the high levels of CM-IgE and Cas-IgE in combination with asthma [11, 24].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, numerous studies have suggested that the component is the best discriminator between persistent and transient CM allergy [6, 8, 11]. Severe reactions to CM can be predicted by the high levels of CM-IgE and Cas-IgE in combination with asthma [11, 24]. Moreover, casein was often found to be the cause of reactions in patients with CM allergy who ate so-called non-dairy products that actually used casein as an extender (e.g., sausage, soups, and stews) [11, 25].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations